SLIM 2012 - Shelf-life International Meeting - Special issue of "Italian Journal of Food Science" - Mancusi, Chiara (Italian Journal of Food Science, 2019)
This Special Issue of the Italian Journal of Food Science collects the presentations given at the “SLIM 2012, Shelf Life International Meeting” organized by the Italian Scientific Group of Food Packaging (GSICA) and Korean Society of Food Science and Nutrition (KFN), held at Changwon, South Korea on May 30-June 1 2012. These papers were reviewed by the Scientific Committee of SLIM 2012 before their presentation but they did not undergo the conventional reviewing system of the Italian Journal of Food Science.